The best seat in second grade - Kenah, Katharine; Carter, Abby (London : Harper Collins Publishers, 2005)
A city of Whos on a speck of dust are threatened with destruction until the smallest Who of all helps convince Horton's friends that Whos really exist.
Keywords: 9; Hamsters -- Juvenile fiction; Museums -- Juvenile fiction